Rancang Bangun Sistem Informasi Keuangan Sekolah Berbabsis Website - Wirawan, Ivan Kurnia; Srirahayu, Agustina; Sopingi, Sopingi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Financial management at Ignatius Slamet Riyadi Surakarta Graphic Vocational School currently still relies on manual methods for recording and reporting Education Development Contributions (SPP), which creates various administrative problems. This manual approach is not time-efficient and is prone to mistakes, data loss, and inaccurate reports. The purpose of this project is to create a financial information system for the school that is web-based. The system designed aims to increase the efficiency and accuracy of managing tuition payments, by providing real-time monitoring features for students and their parents/guardians, as well as assisting school principals in monitoring financial reports. This system development uses a prototype method which involves the stages of design, evaluation, coding, testing and system evaluation. The system can automatically record transactions, lower administrative errors, and expedite the report creation process, according to the testing results. With an easy-to-use interface, this system facilitates access for users according to their roles, namely admin, principal and students. In conclusion, implementing this system can improve financial management in schools, but it requires integration with other school administration systems and increased system security for future development.